Prevalence of Diarrhea Disease and Associated Factors Among Children Under 5 Years in Geshiyaro Project Implementation Sites in Ethiopia: A Cross‐Sectional Study - Zinabu Assefa Alemu; Aderajew Mekonnen Girmay; Kirubel Tesfaye Teklu; Ermias Alemayehu Adugna; Melaku Gizaw Serte; Tsigereda Assefa Alemayehu; Badasa Wagari Likasa; Benjamin Collyer; Zelalem Mehari; Mihretab Salasibew; Getachew Tollera; Masresha Tessema (Health Science Reports)
ABSTRACT Background Globally, infectious diseases such as pneumonia, diarrhea, and malaria are the leading causes of death for children under 5. Diarrheal disease is a significant public health concern and causes the death of approximately 525,000 children under the age of 5 every year. In Ethiopia, studies revealed that the prevalence of diarrhea among children under 5 years is alarming. However, there has been a shortage of studies regarding the predictors of diarrheal disease in Geshiyaro project implementation sites in Ethiopia. Therefore, this study aimed to fill this gap. Methods A community‐based cross‐sectional study was conducted from June to July 2023. A total of 2937 participants were enrolled in this investigation. Descriptive and multivariate logistic regression analysis was performed using STATA version 16. Results The 2‐week prevalence of diarrhea among children under 5 years was 11.8%. The following factors were significantly associated (p < 0.05) with the occurrence of childhood diarrhea: sex of the child (AOR: 1.6; 95% CI, 1.17–2.19), child age in a month (AOR: 0.5; 95% CI, 0.26–0.94), drinking water service (AOR: 2.6; 95% CI, 1.33–5.25), knowledge on diarrhea prevention (AOR: 1.4; 95% CI, 1.05–1.98), open defecation practice (AOR: 1.9; 95% CI, 1.33–2.74), and rotavirus vaccination (AOR: 1.8; 95% CI, 1.20–2.56). Conclusions This study identified several factors contributing to diarrhea. Besides, it also studied and showed a larger number of children who were not receiving basic vaccines. Therefore, the government and partner organizations should implement effective interventions to increase vaccine coverage and reduce diarrhea.